The application of green YF3:Er3+,Yb3+ and red MgSr3Si2O8:Eu2+,Mn2+ layers to remote phosphor LED - My Hanh Nguyen Thi; Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
White light-emitting diodes (WLEDs) with quantum dots (QDs) and phosphor have pulled in huge consideration because of their incredible shading rendering capacity. In the bundling procedure, a QDs film and a phosphor silicone layer will in general be isolated for lessening the reabsorption misfortunes and keeping the QDs surface molecules in a good condition. This examination explored the bundling succession of QDs and phosphor layers to the optical and warm exhibitions of WLEDs. The emitted optical power and PL spectra were estimated and dissected, while an infrared warm imager was utilized to reenact and approve tentatively the temperature fields. The results reveal that at 60 mA, WLEDs with green QDs-on-phosphor type accomplished lumen output (LO) of 1578 lm, with shading rendering record (CRI) of Ra = 60, while the red QDs-on-phosphor type WLEDs exhibited lower LO of 1000 lm, with Ra = 82. In addition, the QDs-onphosphor type WLEDs generated less warmth than the other, and as a result, the most noteworthy temperature in this packaged type was lower than the other. Additionally, its temperature contrast can arrive at 12.3°C. Along these lines, regarding bundling arrangement, the QDs-on-phosphor type is an ideal bundling design to better the optical productivity and shading rendering capacity, as well as lower gadget temperature.